Development of a total dissolved solids (TDS) chronic effects benchmark for a northern Canadian lake. (28th September 2015) - Chapman, Peter M; McPherson, Cathy A
ABSTRACT: Laboratory chronic toxicity tests with plankton, benthos, and fish early life stages were conducted with total dissolved solids (TDS) at an ionic composition specific to Snap Lake (Northwest Territories, Canada), which receives treated effluent from the Snap Lake Diamond Mine. Snap Lake TDS composition has remained consistent from 2007 to 2014 and is expected to remain unchanged through the life of the mine: Cl (45%–47%), Ca (20%–21%), Na (10%–11%), sulfate (9%); carbonate (5%–7%), nitrate (4%), Mg (2%–3%), and minor contributions from K and fluoride. The TDS concentrations that resulted in negligible effects (i.e., 10% or 20% effect concentrations) to taxa representative of resident biota ranged from greater than 1100 to greater than 2200 mg/L, with the exception of a 21% effect concentration of 990 mg/L for 1 of 2 early life stage fish dry fertilization tests (wet fertilization results were >1480 mg/L). A conservative, site‐specific, chronic effects benchmark for Snap Lake TDS of 1000 mg/L was derived, below the lowest negligible effect concentration for the most sensitive resident taxon tested, the cladoceran, Daphnia magna (>1100 mg/L). Cladocerans typically only constitute a few percent of the zooplankton community and biomass in Snap Lake; other plankton effect concentrations ranged from greater than 1330 to greater than 1510 mg/L. Chironomids, representative of the lake benthos, were not affected by greater than 1380 mg/L TDS. Early life stage tests with 3 fish species resulted in 10% to 20% effect concentrations ranging from greater than 1410 to greater than 2200 mg/L. The testing undertaken is generally applicable to northern freshwaters, and the concept can readily be adapted to other freshwaters either for TDS where ionic composition does not change or for major ionic components, where TDS composition does change. Integr Environ Assess Manag 2016;12:371–379. © 2015 SETAC Key Points: Total dissolved solids from mining increasing in a northern Canadian lake. Novel site‐specific toxicity testing conducted to determine a protective chronic effects benchmark. Resident taxa tested representing all components of the food chain (benthos, plankton, fish). Chronic effects benchmark of 1, 000 mg/L will protect lake function while allowing mining to continue.